Association of per- and polyfluoroalkylated substances/heavy metals and bone health in children and adolescents - Wei, Yumeng; Zhang, Yuxiao; Ji, Qiaoyun; Yang, Sufei; Yang, Fan (Frontiers in Public Health, 2024)
Background Research on the correlation between exposure to per- and polyfluoroalkylated substances (PFASs)/heavy metals and bone health during childhood and adolescence is limited. Considering their role as endocrine disruptors, we examined relationships of six PFASs and three heavy metals with bone mineral density (BMD) in children and adolescents using representative samples from the National Health and Nutrition Examination Survey (NHANES). Methods The study included 622 participants aged 12–19. The relationship between single pollutant and lumbar spine and total BMD was studied using linear regression analyses. Additionally, Bayesian Kernel Machine Regression (BKMR) models were applied to assess the joint effects of multiple PFASs and heavy metals exposure on the lumbar spine and total BMD. Results Statistically significant differences were noted in the serum concentrations of perfluorooctanoic acid (PFOA), perfluorooctane sulfonic acid (PFOS), perfluorohexane sulfonic acid (PFHxS), blood lead (Pb), and blood manganese (Mn) between male and female participants (all p < 0.05). Single-exposure studies have shown that Mn was negatively correlated with lumbar spine BMD and total BMD. Multivariate linear regression models revealed that, in the male group, total bone density decreased as the blood PFOA levels [95% CI = (−0.031, −0.001), p = 0.040] and blood manganese levels [95% CI = (−0.009, −0.002), p = 0.004] increased. Similarly, lumbar spine bone density decreased as the blood manganese levels [95% CI = (−0.011, −0.002), p = 0.009] increased. In the female group, total bone density decreased as the serum PFNA levels [95% CI = (−0.039, 0.000), p = 0.048] increased. As shown in the BKMR model, the joint effects of pollutant mixtures, including Mn, were negatively associated with both the lumbar spine and total BMD. Among the pollutants analyzed, Mn appeared to be the primary contributor to this negative association. Conclusion This study suggests that exposure to certain PFASs and heavy metals may be associated with poor bone health. Childhood and adolescence are crucial stages for bone development, and improper exposure to PFASs and heavy metals during these stages could potentially jeopardize future bone health, consequently raising the risk of osteoporosis in adulthood.